Identification of Damage in Press Stations Using the Failure Mode and Effect Analysis (FMEA) Method at PT. Beurata Subur Persada - Abdiel Khaleil Akmal; Iing Pamungkas; Heri Tri Irawan (Jurnal Inotera, 2024)
PT. Beurata Subur Persada (BSP) is a crude palm oil (CPO) producer based in Babah Dua Village, Tadu Raya District, Nagan Raya Regency, Aceh. PT BSP employs 103 people across various production stations, including presses, threshers, sterilizers, and trucks.The Failure Mode and Effect Analysis (FMEA) method is being used in this study to determine damage to PT. Beurata Subur Persada's press station. The FMEA approach is used to assess probable failures in the manufacturing process, determining their severity, frequency of occurrence, and detection capabilities. This study focuses on gathering machine damage data from November 6 to December 6 of 2023 and evaluating it to determine the Risk Priority Number (RPN) value, which will be used to indicate the priority repairs required. This research aims to make recommendations for future damage repair and prevention, as well as improve the company's reliability and efficiency in operations.